2021
DOI: 10.3390/ijerph18157833
|View full text |Cite
|
Sign up to set email alerts
|

BMI Fails to Reflect the Developmental Changes in Body Fatness between Boys and Girls during Adolescence

Abstract: Body mass index (BMI) is thought to reflect excess adiposity in both youth and adults alike. However, the association between BMI and fatness varies, especially as children grow into adults. Thus, the present study sought to address this issue by characterizing how BMI reflects age and sex differences in body fatness in 7–16-year-old children. Methods: This cross-sectional study was conducted with 2150 children and adolescents, aged 7 to 16 years from the city of Santa Cruz do Sul, Brazil. BMI (kg/m2), and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…However, inconsistent results are shown in similar studies by Lisowski et al [ 56 ], who reported no sex differences in the prevalence of overweight in children, and by Kantanista et al [ 57 ], indicating BMI may not be a significant factor for boys or girls when planning health-focused PA programs in adolescents aged 14 to 16 years old. Moreover, Nevill et al [ 58 ] suggested that BMI may not properly reflect changes in body fat percentage. Indeed, these authors confirm that there might be differences in BMI by sex even after adjustment of percent body fat.…”
Section: Discussionmentioning
confidence: 99%
“…However, inconsistent results are shown in similar studies by Lisowski et al [ 56 ], who reported no sex differences in the prevalence of overweight in children, and by Kantanista et al [ 57 ], indicating BMI may not be a significant factor for boys or girls when planning health-focused PA programs in adolescents aged 14 to 16 years old. Moreover, Nevill et al [ 58 ] suggested that BMI may not properly reflect changes in body fat percentage. Indeed, these authors confirm that there might be differences in BMI by sex even after adjustment of percent body fat.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, BMI fails to reflect the developmental changes in body fatness between boys and girls during adolescence (Nevill et al, 2021). Therefore, in the studies, it is inevitable to look for and evaluate indicators of the internal structure of the body.…”
Section: Introductionmentioning
confidence: 99%